2011
DOI: 10.1111/j.1834-7819.2011.01325.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of intrusive luxation in the primary dentition by surgical repositioning: an alternative approach

Abstract: Intrusive luxation is the most common trauma during early infancy which results in the displacement of the tooth into its alveolus. Depending on the severity of the intrusion, the American Academy of Pediatric Dentistry recommends either extraction or spontaneous re-eruption for the primary tooth. This case report provides a brief insight into surgical repositioning as an alternative treatment option for the management of intruded primary tooth in a 4-year-old girl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…1 Two case reports 3435 have shown that immediate surgical repositioning of intruded teeth have shown good prognosis for over an year without development of complications. Among the relevant articles in the present review, two papers have evaluated both surgical repositioning and spontaneous re-eruption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Two case reports 3435 have shown that immediate surgical repositioning of intruded teeth have shown good prognosis for over an year without development of complications. Among the relevant articles in the present review, two papers have evaluated both surgical repositioning and spontaneous re-eruption.…”
Section: Discussionmentioning
confidence: 99%
“…Though with a few case series we cannot assess the benefits of surgical repositioning, it can be done in a situation when there is no impact of primary root on permanent tooth bud, when there is moderateto-severe intrusion, when the child is cooperative, and when both child and parent can be motivated to maintain oral hygiene. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Intrusive luxation is one of the most common types of trauma, accounting for 8%-22% of all luxation injuries of the primary anterior teeth, 1 and studies performed in different countries have reported a prevalence of up to 54%. [2][3][4] Intrusive luxation results in axial displacement of the tooth into the alveolar bone. This may cause damage to the periodontal structures and pulp through crushing and rupture of the fibers of the periodontal ligament and vascular supply, with rupture of the neurovascular supply to the pulp.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have evaluated the prognosis of intruded teeth. 3,9,[14][15][16] The present study sought to enhance knowledge on the influence of the degree of intrusion on the prognosis of affected teeth and permanent successors. The aim of study was to assess intrusive luxation of primary teeth and the influence of the degree of intrusion on the frequency of spontaneous re-eruption and on the occurrence of sequelae.…”
Section: Introductionmentioning
confidence: 99%
“…Primary tooth intrusion may result in a variety of pathological alterations to permanent teeth, including hypoplasia; crown dilaceration; root angulation or dilaceration; partial or complete arrest of root formation; sequestration of the permanent tooth germ; and disturbances in eruption 19 . Depending on the severity of the intrusion, the American Academy of Pediatric Dentistry recommends either extraction or spontaneous re-eruption for the primary tooth 20 . In most cases, treatment of complicated injuries in primary dentition has been limited to extraction of the affected tooth 13,21 .…”
Section: öZetmentioning
confidence: 99%